Diagnostics and analytical modelling for permanent-magnet synchronous machines - Skarmoutsos, Giorgos (The University of Edinburgh, 2023)
This dissertation proposes a novel diagnostic technique that utilises two air-gap search-coils which couple magnetically only under faulty conditions and can detect all the faults occurring in permanent-magnet machines. Furthermore, an existing search-coil-based method was expanded for detecting partial demagnetisation. A formula was developed which detects the frequency spectrum signatures under dynamic eccentricity, again in permanent-magnet machines. In the second stage, a magnetic field calculation algorithm was developed for the two basic rotor geometries of permanent-magnet synchronous machines, i.e. surface-mounted and surface-inset. The dissertation was divided into four parts and seven chapters. The first part is devoted on talking about the motivation that lead to work on this research subject and the objectives that this dissertation aims to satisfy. The fundamentals of permanent-magnet machines are also presented along the machine topologies that are used in this thesis to prove various methodologies and validate algorithms. In the second part, the diagnostic aspect of permanent-magnet machines is examined initially by doing a detailed literature review. The purpose of this comprehensive literature review is to become acquainted with the state-of-the-art fault diagnostic methods, identify what problems the existing methods cannot solve, and use the material for inspiration to develop a new diagnostic method. Afterwards, the review oriented the research towards the direction of air-gap flux monitoring, having single and double search-coil configurations validated using a Finite-Element Analysis software and experimental measurements taken by machines operating in a laboratory environment. The faults studied are partial demagnetisation, inter-turn fault and static-, dynamic- eccentricity. Lastly, based on the gaps found in the literature review, a method is presented to calculate the harmonics excited by the dynamic eccentricity fault. The third part of this thesis dealt with calculating the magnetic field distribution in radial-flux permanent-magnet machines with the surface, -mounted and -inset magnets. What triggered this research are the possibilities that come from having the components of the magnetic field distribution for every angle of the stator and rotor magnetic fields. This technique makes it possible to calculate all operational parameters that project the machines' performance. These are the Back-EMF and the types of torque, cogging, electromagnetic and reluctance. Finite-Element Analysis was used to validate the analytical subdomain model with great success. The fourth and last part of this dissertation summarises the conclusions and contributions of this work along with leads for future work.
Keywords: permanent-magnet synchronous machines; air-gap search-coils; detecting partial demagnetisation; magnetic field calculation algorithm; basic rotor geometries; Back-EMF; torque, cogging; Finite-Element Analysis